STRATEGI PERUSAHAAN BUNGA KERING CV. MATAHARI HANDICRAFT FLOWERS DI DUKUH MANTRIJERON, KOTA YOGYAKARTA - Anisa Prastiari; Indah Widowati; Juarini Juarini (Jurnal Dinamika Sosial Ekonomi, 2015)
This research aims to analyze strategy choices of CV. Matahari Handicraft Flowers in order to face present and further competition, based on analysis approach of SWOT (Strenghts, Weakness, Opportunity, Threat). Matrix of SPACE (Strategic Position and Action Evaluation), Matrix of IE (Internal Eksternal), and Matrix of Grand Strategy; to know the right strategy decision to be applied in CV. Matahari Handicraft Flowers. Basic method used is descriptive method. Implementation method uses case study method. Data varieties used are primary and secondary data. Data source is obtained from the owner of CV. Matahari Handicraft Flowers, references, and other related institutions. Technique of collecting the data is by observation, questionnaire, interview, references study and notes taking. To analyze right strategy choices in CV. Matahari Handicraft Flowers in order to face present and further competition, SWOT Matrix, SPACE Matrix, IE Matrix and Grand Strategy Matrix are used. As for knowing the right development strategy decision applied in CV. Matahari Handicraft Flowers, Quantitative Strategic Planning Matrix (QSPM) is used. The result of this research showed, that CV. Matahari Handicraft Flowers had been presented in strategic SO based on SWOT Matrix, agresif condition based on SPACE Matrix, first, second, fourth cell (Grow and Build) based on IE Matris, first quadran based on Grand Strategy Matrix. Market penetration is an appropriate strategy to expand CV. Matahari Handicraft Flowers. Keywords: Company strategies, Dried Flowers, CV. Matahari Handicraft Flowers.